KARAKTER TOKOH UTAMA DALAM NOVEL KUBAH KARYA AHMAD TOHARI: KAJIAN PSIKOLOGI SASTRA - Amri, Amri; Effendy, Chairil; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This research is motivated by the desire to find the main character in the novel Kubah Karya Ahmad Tohari. A common problem in this research is "What is the character of the main character in the novel Kubah Karya Ahmad Tohari ?. This study uses descriptive methods, qualitative research forms, and uses behavioristic psychological approaches. Based on the results of data analysis it can be concluded that: 1) through the thoughts of the main characters in the novel Kubah Karya Ahmad Tohari can be found humble characters, steadfast, confused, friendly, gentle/compassionate, feeling, loving and jealous 2) through the behavior of characters in the novel Kubah Karya Ahmad Tohari can be found good-hearted, diligent, clever, and helper 3) through the reaction of the main character in the novel Kubah Karya Ahmad Tohari can be found in awe, patience, regret, doubt, rebellion, respect and fear. The results of this study can be implemented in learning Indonesian in high school, especially for students of class XII semester II.Â Keywords: Character, Main Figures, Novel